Some kinematic properties of complex eigenvalues in 3D homogeneous flows - Iacopini, D.; Carosi, R. (TRABAJOS DE GEOLOGÍA, 2009)
A mathematical investigation on some kinematic properties of 3D homogeneous flows defined by complex eigenvalues is presented. We demonstrate by mean of simple algebra analysis, that in a 3D flow system a clear threshold between pulsating and non-pulsating fields does not exist. This implies that the existence of a stable or pulsating pattern in 3D flow is not simply imposed by the kinematic vorticity numbers. Moreover, we show theoretically that a 3D flow path having complex eigenvalues could evolve into a stable flow path. These results are applied to the kinematic analysis of some non-dilational and dilational monoclinic and triclinic flows.